Engaging Stakeholders to Develop a Patient-centered Research Agenda: Lessons Learned From the Research Action for Health Network (REACHnet). Issue 10 (October 2018) - Haynes, Sarah C.; Rudov, Lindsey; Nauman, Elizabeth; Hendryx, Lindsay; Angove, Rebekah S.M.; Carton, Thomas
Abstract : Background: Patient-centered research requires a focus on the needs and priorities of patients. Because patient engagement can result in the discovery of important topics not currently prioritized by research programs, topic generation, and prioritization activities conducted with patients, caregivers, and other stakeholders are essential. To develop patient-centered research agendas for obesity and diabetes, the Research Action for Health Network conducted topic generation and prioritization activities with multistakeholder research advisory groups. Objectives: The purpose of this case study was to demonstrate how methods for engaging patients in topic generation and prioritization can be implemented in practice for the development of a patient-centered research agenda. Research Design: Four multistakeholder groups comprising patients, clinicians, and researchers met 4–5 times between November 2014 and July 2015 to generate and prioritize topics for obesity and diabetes research. Topics were prioritized using an iterative engagement process, in which themes were identified and resulting topics were refined and ranked over multiple meetings. Participants: Sixty-four patients, clinicians, and researchers participated in 2 obesity and 2 diabetes advisory groups. The majority of participants (64.0%) were patients, followed by clinicians (23.4%), researchers (9.4%), and parents of children with diabetes (3.1%). Results: Ten and 12 priority topics were identified for obesity and diabetes, respectively. The resulting research agendas were disseminated to patients, researchers, and clinicians. Conclusions: Patient engagement has the potential to enrich our understanding of patient priorities for research. The results from this process suggest that convening in-person multistakeholder groups can be an effective way to generate research topics that reflect patients' priorities. Engagement strategies should be focused not only on the development of patient-centered research topics but also on the implementation of these topics into research studies.